A gene deletion ending within a complex array of repeated sequences 3' to the human beta-globin gene cluster. - Henthorn, P S (1986)
A DNA fragment containing the deletion junction region from an Indian individual with a type of hereditary persistence of fetal hemoglobin has been cloned. Using a probe isolated from this deletion-spanning clone, we located the 3' breakpoint of the deletion in normal DNA to a region 30 kilobase pairs (kb) downstream of the beta-globin gene. The deletion removes 48.5 kb of DNA. Sequences of the deletion junction and of the normal DNA surrounding the 3' breakpoint were determined and compared to the previously determined sequence of the normal DNA surrounding the 5' breakpoint. This comparison shows that the deletion was the result of a nonhomologous recombinational event, although there is a 5-base-pair (bp) region of local homology between the normal DNAs at their breakpoints. The 5' deletion breakpoint occurs in the Alu family repeat 3' to the A gamma-globin gene. The 3' breakpoint is located within a region that contains the following: a portion of an L1 (Kpn I) repeat, a perfect 160-bp palindrome, and a set of 41-bp direct repeats that are found elsewhere in the human genome. A variation in restriction fragment lengths was observed in this region in one family.